OPTIMIZING SOCIAL MEDIA CONTENT AS A MARKETING STRATEGY TO INCREASE ENGAGEMENT AT KYOU HOBBY SHOP - Putra, Candra Lucas Diansa; Prasojo, Bayu Hari (Antis-publisher, 2026)
Objective: This study aims to examine the effectiveness of short-form video content on Instagram Reels as a digital marketing strategy to increase customer engagement at Kyou Hobby Shop, a business specializing in hobby-related products. Method: The research employed a descriptive qualitative approach using a case study design conducted during a campus internship program. Data were obtained through direct involvement in content production, observation of audience interactions, and analysis of engagement metrics. Various types of video content were developed, including product reviews, tutorials, and interactive videos tailored to audience interests and platform characteristics. Results: The findings indicate that short-form video content significantly improves engagement indicators, particularly views, comments, and shares, compared to static content. Additionally, the consistent delivery of relevant and engaging information contributed to strengthening customer loyalty and fostering more interactive communication between the business and its audience. Novelty: This study offers practical empirical evidence on how internship-based content creation strategies can be systematically utilized to optimize Instagram Reels for small retail businesses, highlighting the integration of experiential learning and digital marketing practices as an effective approach to enhancing social media engagement.